Isoleucine Accumulation by Regulatory Mutants of Serratia marcescens: Lack of Both Feedback Inhibition and Repression - Kisumi, Masahiko (1972)
Double mutants of Serratia marcescens resistant to isoleucine hydroxamate and α-aminobutyric acid accumulated large amounts of isoleucine in a salts-sugar medium and lacked both feedback inhibition and repression of the isoleucine biosynthesis.